The Liberation of Judaea and Early Maccabaean Diplomacy with Rome according to Justin (36.3.9), Diodorus (40.2/4) and Caesar (Jos. Ant. Jud. 14.10.6 [205]) - Coşkun, Altay (Anabasis. Studia Classica et Orientalia, 2018)
<p class="CDt4Ke zfr3Q" dir="ltr" style="background-color: transparent; line-height: 1.92; margin-bottom: 0; margin-left: 0; margin-top: 11pt; text-align: justify; text-indent: 15pt; white-space: normal; border: none; padding: 0;">Justin (36.3.9), Diodorus (40.2/4) and Julius Caesar (quoted by Josephus, Ant. Jud. 14.10.6 [205]) are the only non-Jewish sources to mention Roman-Judaean diplomacy in the 2nd century BCE. Some scholars have adduced them to reject the claim of 1 Macc 8 that Judas Maccabee established friendship and alliance with Rome in 161 BCE – unduly so, as this article sets to argue. Justin has often been misunderstood as attesting only a grant of freedom to Judaea rather than a treaty, but this would be misreading the anti-Roman rhetoric. What is more, Justin mentions that amicitia began under King Demetrius, and different to previous interpretations, the context compels us to identify him with Demetrius II Nicator during his second tenure (129–125 BCE). Diodorus has been read as evidence for freedom under Demetrius I Soter (162–150 BCE), but the transmitted text does not speak of a Demetrius or a revolt from the Seleucids; what it does is alluding to Judaean diplomacy with Rome under John Hyrcanus I (135–105 BCE). Caesar states that Joppa was a possession of the Judaeans before the Romans first made a treaty with them. Since the city was taken by Jonathan and Simon for the first time in 150 BCE, Caesar reflects the same unawareness of the first Judaean-Roman treaty of friendship and alliance made under Judas. Rather than providing independent evidence against the claim of 1 Macc 8, the three sources under examination seem to be traces of one now-lost Graeco-Roman tradition (most likely Posidonius) that let Judaean-Roman amicitia begin under John Hyrcanus I in ca. 128 BCE.